Healthy crops to help sustainable, healthy diets: A guide to healthy vegetable seedling sowing in Bangladesh - Rahaman, Md. Arifur; Cheesman, Stephanie; Parupalli, Bharathi; Hossain, Md. Shakhawat; Ferdous, Zannatul; Huda, Md. Shamsul; Krupnik, Timothy J. (TAFSSA, 2023)
For the cultivation of many vegetables, growing seedlings is one the most important parts of the crop production cycle. Healthy seedlings are the first step towards growing a healthy, high value vegetable crop. Vegetables, particularly leafy greens and orange, yellow, or red colored vegetables are also very beneficial for human health. Growing seedlings can help ensure good crop establishment and reduce farm production risks by lowering the time crops are exposed to the field.